2020
DOI: 10.21106/ijma.324
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Early Newborn Care: A Descriptive Analysis of Recent Births in Nigeria

Abstract: Background or Objectives: The neonatal period, the first 28 days of life, is the most critical period for child survival. In 2017, 214,000 children in Nigeria died during the neonatal period. Newborn care practices play a key role in preventing these deaths. The aim of this study was to examine the association between delivery location and early newborn care in Nigeria. Methods: Data from the 2013 Nigeria Demographic and Health Survey were analyzed. The main exposure variable was delivery location (home,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…The current study showed that first postnatal hour breastfeeding was practiced by 344 (89.6%). In agreement with this frequency, previous studies approved the benefit of the early initiation of breastfeeding [ 6 , 7 , 27 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The current study showed that first postnatal hour breastfeeding was practiced by 344 (89.6%). In agreement with this frequency, previous studies approved the benefit of the early initiation of breastfeeding [ 6 , 7 , 27 ].…”
Section: Discussionsupporting
confidence: 73%
“…Thermal care components are the immediate wrapping and drying of the baby, delaying bathing for 24 h, and skin-to-skin contact (SSC) [ 5 ]. Breastfeeding and SSC have been proven to be effective, low-cost interventions to save newborn lives [ 6 ]. Despite this, SSC practice was reported to be suboptimal universally [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 In a recent study in Nigeria, a neighboring country to Benin, it was reported that women who gave birth at a public hospital were more likely than their counterparts who gave birth at home to initiate breastfeeding early, receive breastfeeding support, and have their newborns' cord examined by a health professional. 20 A likely explanation for the finding in the current study may be the quality of care provided in public hospitals. In a publication on the assessment of the health system in Benin, it was reported that few incentives exist in the public health care system (public hospitals and clinics) to offer quality care, and many of the in-built incentives lead to reduced quality of care.…”
Section: Associations Between Birth Location and Early Newborn Care Practicesmentioning
confidence: 76%
“…These estimates are consistent with literature from other sub-Saharan Africa countries where indicators of early newborn care need improvement. 20,21 The suboptimal rates of breastfeeding initiation and support could be because of a lack of emphasis on breastfeeding at the national policy level in combination with a shortage of adequately trained health professionals to provide skilled support. 3,22 We also observed that the location of childbirth was associated with breastfeeding support and cord examination, but not early initiation of breastfeeding.…”
Section: Associations Between Birth Location and Early Newborn Care Practicesmentioning
confidence: 99%
“…[5][6][7] Cultural practices relating to newborn care remain prominent in most sub-Saharan African and Southeast Asian communities, [8,9] and can expose newborns to the risk of infection, hypothermia, and inadequate feeding, due to unhygienic and harmful practices. For example, Olorunsaiye et al [10] reported that two-thirds of mothers delivered at home under unhygienic conditions.…”
Section: Introductionmentioning
confidence: 99%